2018
DOI: 10.4236/psych.2018.99132
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Analysis of the Links among Life History, Reproductive Strategy, Autism-Spectrum Quotient, and Quality of Life

Abstract: The present study explores the links among life history, reproductive strategy, autism-spectrum quotient, and quality of life. Our 235 participants (167 women and 68 men, aged 19-54) filled four instruments: Life History Survey (LHSurv), MINI-K, Autism-spectrum Quotient (AQ), and Satisfaction with Life Scale (SWLS). A cluster analysis was carried out in which the respondents' answers to particular LHSurv items were used as variables in the clustering process. The next step in the analysis was to compare the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 76 publications
0
0
0
Order By: Relevance
“…These indicated the annual species in the RWLFZs adopt the R adaptation strategy with fast-growing, effectively dispersing, short lifespan and quickly acquiring and investing resources by altering leaf morphology such as expanding leaf area into the production of offspring in the primary stage of plant community succession. In habitats with long-term poor conditions, frequent and severe disturbances in the RWLFZs, the resources captured could be quickly reintroduced or redistributed for rapid settlement in the area, annual plants would allocate much more to reproduction in order to be able to maximize the fitness gaining on reproductive output as soon as the environment allows them [46], and plant individuals are relatively small, short life history and high fertility, with annuals germinating in spring and fructifying in autumn or annuals germinating in late winter and fructifying in summer, while in the high elevation areas of the RWLFZs, annual herbs, such as X. sibiricum, grows tall, allocates much more to vertical vegetative growth at the expense of lower reproductive output in order to be able to maximize this species fitness. A progressive replacement of the R-strategists by the SC or the CSR strategists would occur in the long-term succession stages of naturally recovered plant communities, and for perennial plants such as C. dactylon, it adopted the rapid capture and monopolization of resources with the spatially dynamic foraging of roots and shoots according to the C adaptation strategy of the competitive CSR model of Grime.…”
Section: Plant Community Characteristics and Their Ecological Adaptat...mentioning
confidence: 99%
“…These indicated the annual species in the RWLFZs adopt the R adaptation strategy with fast-growing, effectively dispersing, short lifespan and quickly acquiring and investing resources by altering leaf morphology such as expanding leaf area into the production of offspring in the primary stage of plant community succession. In habitats with long-term poor conditions, frequent and severe disturbances in the RWLFZs, the resources captured could be quickly reintroduced or redistributed for rapid settlement in the area, annual plants would allocate much more to reproduction in order to be able to maximize the fitness gaining on reproductive output as soon as the environment allows them [46], and plant individuals are relatively small, short life history and high fertility, with annuals germinating in spring and fructifying in autumn or annuals germinating in late winter and fructifying in summer, while in the high elevation areas of the RWLFZs, annual herbs, such as X. sibiricum, grows tall, allocates much more to vertical vegetative growth at the expense of lower reproductive output in order to be able to maximize this species fitness. A progressive replacement of the R-strategists by the SC or the CSR strategists would occur in the long-term succession stages of naturally recovered plant communities, and for perennial plants such as C. dactylon, it adopted the rapid capture and monopolization of resources with the spatially dynamic foraging of roots and shoots according to the C adaptation strategy of the competitive CSR model of Grime.…”
Section: Plant Community Characteristics and Their Ecological Adaptat...mentioning
confidence: 99%
“…These indicated that the annual species in the RWLFZs adopt the R adaptation strategy of being fast-growing, able to effectively disperse with a short lifespan and quickly acquiring and investing resources by altering leaf morphology, including expanding the leaf area into the production of offspring in the primary stage of plant community succession. In habitats with long-term poor conditions and frequent and severe disturbances in the RWLFZs, the resources captured could be quickly reintroduced or redistributed for rapid settlement in the area; annual plants would allocate much more to reproduction in order to be able to maximize the fitness gain from reproductive output as soon as the environment allows them [51]. Plant individuals are relatively small and have a short life history and high fertility, with annuals germinating in spring and fructifying in autumn or annuals germinating in late winter and fructifying in summer, while in the high elevation areas of the RWLFZs, annual herbs, such as X. sibiricum, grow tall and allocats much more to vertical vegetative growth at the expense of lower reproductive output in order to be able to maximize this species fitness.…”
Section: Plant Community Characteristics and Their Ecological Adaptat...mentioning
confidence: 99%